The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1037/bul0000224
|View full text |Cite
|
Sign up to set email alerts
|

The manipulation of affect: A meta-analysis of affect induction procedures.

Abstract: Affect inductions have become essential for testing theories of affect and for conducting experimental research on the effects of mood and emotion. The current review takes stock of the vast body of existing literature on affect induction procedures (AIPs; also referred to as mood inductions) to evaluate the effectiveness of affect inductions as research tools and to test theories of affect (e.g., the bipolarity hypothesis, negativity bias, positivity offset, and theories of emotionality and gender) using meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
91
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 116 publications
(144 reference statements)
12
91
2
Order By: Relevance
“…Finally, although the hypothesized model fit the data well, the order of the model elements might be organized differently as elements in T1 and T2 covered responses to the same stimulus, i.e., a film clip and the partner's capitalization attempt, respectively. Finally, the effects of clips on positive and negative affect that we observed were smaller than the average effects found in other studies (Joseph et al, 2020). Responders might have been emotionally engaged in the social interaction waiting for their partner's results.…”
Section: Limitations and Future Directionscontrasting
confidence: 90%
“…Finally, although the hypothesized model fit the data well, the order of the model elements might be organized differently as elements in T1 and T2 covered responses to the same stimulus, i.e., a film clip and the partner's capitalization attempt, respectively. Finally, the effects of clips on positive and negative affect that we observed were smaller than the average effects found in other studies (Joseph et al, 2020). Responders might have been emotionally engaged in the social interaction waiting for their partner's results.…”
Section: Limitations and Future Directionscontrasting
confidence: 90%
“…Third, regarding emotional induction, in addition to the autobiographical memory method used by DeSteno et al [7], we also used emotional video clips, which has been demonstrated to be the most effective way of inducing emotions in the lab [12,21]. The manipulation check also showed that participants in the anger condition expressed more anger than those in the sadness and the neutral conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were encouraged to empathize with and relate to the persons portrayed in the clips. Meta-analyses have shown several mood induction procedures to be effective, but especially the combination of film clips with the instruction to empathize with the characters [33,34]. The efficacy of the different film clips in inducing the desired mood was piloted in advance (N negative group = 13; N positive group = 15; N neutral group = 13).…”
Section: Plos Onementioning
confidence: 99%